2019
DOI: 10.3329/bjsir.v54i4.44573
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of germinated and non-germinated cereals : A comparative study

Abstract: Cereal grains play an important role in human nutrition which is useful both for infants and adults. The practice of germination of cereal grains has become popular now-a-days. The present research was carried out to study the functional properties of germinated and non-germinated cereal flours (wheat, maize, sorghum). Bulk density and tapped density were increased in germinated maize but decreased in germinated sorghum and wheat. In germinated wheat and sorghum flour, carr index, foaming capacity, foaming sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Foaming capacity (FC) and foam stability (FS) are other functional attributes of protein globules highly desired in a colloidal food system. With the interfacial area created by a protein to accommodate air bubbles, foaming ability increases and if the protein films are less flexible and easily collapsed the air bubbles thus formed cannot retain, leading to lower foam stability [ 12 ]. Table 5 represents the FC and FS of non-germinated and germinated seed flours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Foaming capacity (FC) and foam stability (FS) are other functional attributes of protein globules highly desired in a colloidal food system. With the interfacial area created by a protein to accommodate air bubbles, foaming ability increases and if the protein films are less flexible and easily collapsed the air bubbles thus formed cannot retain, leading to lower foam stability [ 12 ]. Table 5 represents the FC and FS of non-germinated and germinated seed flours.…”
Section: Resultsmentioning
confidence: 99%
“…It not only affects the anti-nutrients but also affects nutrients such as amino acids, carbohydrates and dietary fiber content. The starch content, fat content, anti-nutrients such as phytate and tannin, dry matter content and bulkiness are reduced during the germination process [ 12 ]. Protein, fat and starch digestibility are improved during germination, as reported in previous studies [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sometimes this flour is produced from malted corn. Previous work has shown that sprouting cereals and legumes improves the quality of their products [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%